الوساطة الجزائية كآلية لحماية الطفل الجانح في القانون الجزائري - نين, عمارة (جامعة الوادي University of Eloued, 2019)
ملخص: تهدف هذه الدراسة إلى البحث حول موضوع حماية الطفل باستخدام الوساطة الجزائية، وقد استحدث المشرع الجزائري هذا الأسلوب بموجب الأمر رقم: 15/02 المؤرخ في 23 يوليو 2015م المعدل والمتمم لقانون الإجراءات الجزائية رقم: 66/155، وكرس بدوره هذه الآلية كحماية للطفل الجانح في قانون حماية الطفل رقم: 15/12 المؤرخ في 15 يوليو 2015م. وقد إتجه المشرع الجزائري للأخذ بنظام الوساطة كبديل عن الدعوى العمومية، وهو أسلوب جديد يتماشى مع التطور الحاصل في مجال العدالة الجنائية، والذي صار يسعى للإصلاح أكثر من تسليط العقوبة، وتتضمن هذه الدراسة البحث في مفهوم الوساطة الجزائية من خلال بيان تعريفها وأطرافها وأهدافها، وكذا بيان إجراءاتها وآثارها. Abstract: This study aims to discuss the issue of child protection using the criminal mediation system , the Algerian legislator adopted this method according to order No. 15/02 of July , 15th 2015 amending and supplementing the criminal procedures code No. 66/155, also it has devoted this mechanism to protect the delinquent child in the Child's Protection Act No. 15/12 of July , 15th 2015 , the Algerian legislator has tended to introduce the mediation system as a substitute for public prosecution, which is a new method responding to the development of criminal justice field which had become to seek for reform more than punishment, the present study includes research on the concept of criminal mediation through indicating its definition , parties , objectives, Procedures and effects.
Keywords: الوساطة الجزائية، حماية الطفل، الإجراءات الجزائية، الوسيط، الضحية; criminal mediation; child protection; criminal procedures; mediator; victim